The role of rifaximin therapy in patients with irritable bowel syndrome without constipation. (July 2011) - Schey, Ron; Rao, Satish SC
Evaluation of: Pimentel M, Lembo A, Chey WD et al. Rifaximin therapy for patients with irritable bowel syndrome without constipation. N. Engl. J. Med. 364(1), 22–32 (2011). Alterations in gut flora may play an important role in the pathophysiology of bowel symptoms, especially in patients with irritable bowel syndrome (IBS). If so, antibiotics that affect gut flora may offer a novel approach for the management of patients with IBS. Here, we discuss the results of two identically designed, double-blind, placebo-controlled trials (TARGET 1 and TARGET 2) of a poorly absorbed antibiotic, rifaximin, in patients with IBS. In these studies, 1260 patients (females 76.1 and 72.1%, respectively) who had IBS without constipation were randomized to receive either rifaximin 550 mg or placebo, three-times daily for 2 weeks. Subsequently, daily symptoms were assessed and patients were followed up for 10 weeks. The primary outcome measure – adequate relief of global IBS symptoms during the first 4 weeks after treatment – was met in significantly more patients who received rifaximin than placebo (p < 0.001). In addition, more patients in the rifaximin group than in the placebo group (p < 0.001) reported an adequate relief of bloating, and an improvement in abdominal pain and stool consistency – secondary outcome measures. The incidence of adverse events with rifaximin was similar to placebo, and the drug was well tolerated. In summary, a 2-week course of rifaximin provided significant relief of IBS symptoms, as well as bloating and abdominal pain.